Response surface methodology for optimization studies of microwave-assisted hydrodistillation of essential oil from Vietnamese Citrus aurantifolia (Lemon fruit) - Tran, Thien Hien; Lam, Tri Duc; Nguyen, Van Tien; Dao, T. P.; Nhan, Le Thi Hong; Toan, Tran Quoc; Vo, Dai-Viet N.; Anh Vy, Tran; Bui, Le Minh (IOP Publishing, 2019)
In this study, microwave-assisted hydrodistillation extraction technique was applied to extract the essential oil from Vietnamese Citrus aurantifolia (Lemon fruit). The optimal conditions for microwave-assisted extraction of lemon fruit oil was determined by response surface methodology. A central composite design (CCD) was used to estimate the effects of three independent variables plant material to extraction time (B: 30, 60, 90 min), microwave power (C: 300, 450, 600 W), and solvent ratio (A: 2, 3, 4 mL/g)., and on the extraction yield of Lemon fruit oil. The optimal extraction conditions of Citrus aurantifolia oil was plant material to solvent ratio 2.80 mL/g, extraction time 63.29 min and microwave power 477.82W. The maximum Lemon fruit oil yield was 2.427%. Under the extraction condition, the experimental values matched with the anticipated results by analysis of variance. It showed high fitness of the model used and the benefit of response surface methodology for optimizing and indicate the expected extraction condition.